PENGARUH PENDIDIKAN KESEHATAN PADA SISWA DAN PETUGAS KEBERSIHAN TERHADAP KEPADATAN JENTIK DI SEKOLAH DASAR WILAYAH KECAMATAN TEMBALANG - Ayun Robi'atul Adawiyah; Martini Martini; Retno Hestiningsih; Praba Ginandjar (Fakultas Kesehatan Masyarakat Universitas Diponegoro, 2016)
Dengue hemorrhagic fever is an infectious disease which becomes one of the most important public health problems in Indonesia. IR DBD Semarang in 2015 was 98.61 per 100,000 population. School is a potential place in the spread and transmission of dengue disease. The objective of this study is to analyze the effect of health education on students and janitors. This research is a quasi-experimental design with pretest-posttest control group design. The samples studied there were 6 primary schools, 3 samples the experimental group and 3 samples the control group. Data were analyzed using t test independent sample and Mann Whitney. The results showed that there is significant differences knowledge of students between control group and experimentation (p = <0.001). So also with the attitude of students that there are significant differences between the experimental and control groups, p = 0.013. On knowledge, attitude and practice of janitors there is no significant difference between the control group and the experimentation, the views of p = 0.184 and 0.317. The density of larvae, there is significant difference Container Index (CI) between control group and experimentation (p = 0,015). House Index (HI) has decreased, but above the standard (> 5%) and Larvae Free Index (ABJ) has increased, but still below the standard (<95%). The conclusion of this research, there is the effect of health education on the knowledge and attitude of students, Container Index (CI) but there isn’t effect on the knowledge, attitude and practice of primary school's janitors..